Ni jedan ljudski klon ne može biti normalan - Rudež, Tanja (Array, 2008)
Prof. Dr. Davor Solter, the director of the Max Planck Institute for immuno-biology in Freiburg, is one of the internationally most highly respected scientists in the field of mammal cloning. Davor Solter, who hails from a prominent Zagreb family of physicians, also opted to take up studies at the Faculty of Medicine where he graduated in 1965. He received his master's degree and doctorate in the field of biology and has studied early mammalian development from the start of his career as a researcher. He has lived abroad since 1973. He has lectured in Zagreb on several occasions at advanced molecular and cell medicine courses organised by the Mayo Clinic held in conjunction with the Third Euro-American School of Forensic Genetics. Among other things, Dr. Solter says: For now everything indicates that there are no normal clones and I therefore believe that it is exceedingly irresponsible to attempt the cloning of a human